Answer:
Explanation:
1) y = 2x ----------(I)
x + y = 6 -----------(II)
Plug in y =2x in equation (II)
x + 2x = 6 {Add like terms}
3x = 6
x = 6/3
x = 2
Plugin x = 2 in (I)
y = 2*2
y = 4
Check:
LHS = x +y
= 2 + 4
= 6 = RHS
2)5x + 10y = 3 ------------(I)
x = (-1/2) y ------------(II)
Substitute x = (-1/2)y in (I)
![5*(-1)/(2)y + 10y = 3\\\\(-5)/(2)y+ (10*2)/(1*2)y = 3\\\\(-5)/(2)y+(20)/(2)y=3\\\\(-5+20)/(2)y = 3\\\\(15)/(2)y=3\\\\ y = 3*(2)/(15)\\\\ y = (2)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/pt38x2sbt3mn04hns6m6y7cw4lps2kn7nz.png)
Substitute y = (2/5) in equation (II)
![x = (-1)/(2)*(2)/(5)\\\\x = (-1)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9aqowbhxbnix8tzdmgs0hkj6pcfrxq3r2n.png)
Check:
Substitute x and y value in equation (I)
![LHS = 5*(-1)/(5)+10*(2)/(5)\\\\ = -1 + 2*2\\\\ = -1 + 4\\ = 3 = RHS](https://img.qammunity.org/2022/formulas/mathematics/high-school/bvetor8kzhv9b2bkiv34nw735g50puti8a.png)
3) y - x = 3x + 2
y = 3x + 2 + x
y = 4x + 2 ---------------(I)
2x + 2y = 14 - y
2x + 2y +y = 14
2x + 3y = 14 ------------------(II)
Substitute y = 4x + 2 in equation (II)
2x + 3(4x +2) = 14
2x + 3*4x + 3*2 = 14
2x + 12x + 6 = 14
14x + 6 = 14
14x = 14 - 6
14x = 8
x = 8/14
x = 4/7
Substitute 'x' value in (I)
![y = 4*(4)/(7) +2\\\\y = (16)/(7)+2\\\\y= (16)/(7)+(2*7)/(1*7)\\\\y=(16)/(7)+(14)/(7)\\\\y=(30)/(7)](https://img.qammunity.org/2022/formulas/mathematics/high-school/4wyfyk3dx65mey5x45b0r9o9jcy168eknf.png)
Check:
![LHS = 2x + 3y\\\\ = 2*(4)/(7)+3*(30)/(7)\\\\ = (8)/(7)+(90)/(7)\\\\=(8+90)/(7)\\\\=(98)/(7)\\\\=14 = RHS](https://img.qammunity.org/2022/formulas/mathematics/high-school/2gqh1o62csm9z008mfomj5twuai67bd3v5.png)